The impact of applying instructional design principles on students’ attitudes towards the learning content - Elkilany, Elsayed A. (Journal of Arab & Muslim Media Research, 2015)
Abstract The aim of this empirical study is to measure the impact of applying instructional design principles on students’ attitudes towards learning content. A course entitled ‘Print Quality Control’ offered in the study plan of the Department of Printing, Publishing and Packaging at the Faculty of Applied Arts, Helwan University in Egypt, was selected for the conduct of this experimental work. The course was taught to Group (A) in spring 2008 academic semester. Students’ attitudes towards the following four variables were measured: ‘clarity of course objectives’, ‘appropriateness of the content to the objectives’, ‘information presentation’ and ’ease of understanding the content’. The results of the study in this phase revealed shortcomings in the four variables, as 68 per cent of the students appreciated the clarity of course objectives, 73.5 per cent the appropriateness of the content to the objectives, 70.5 per cent the information presentation and finally 61.5 per cent the ease of understanding the content. Based on the earlier findings, the course was then updated and two importantn analyses were conducted: the first was analysis of the course learning outcomes, and the second was analysis of the updated content. Thereafter and to fill in the gaps found in the original course, a new course design was developed using media and e-learning development tools, including Adobe Photoshop, Adobe Premiere, Adobe Director, Adobe Flash and Course Genie. This course design was achieved through the application of instructional design principles within a frame of learning theories and the systematic development of the learning materials. The new course design was then validated by ten experts using the BACMAN model and got an average of 4.1 out of 5; it was subsequently published through the Blackboard Learning Management System and taught to Group (B) in spring 2009 academic semester. An analysis of students’ attitudes in Group (B) revealed noticeable improvements in relation to the same variables; 100 per cent of the students appreciated the clarity of course objectives, 100 per cent the appropriateness of the content to the objectives, 83.3 per cent the information presentation and finally 100 per cent the ease of understanding the content.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9qYW1tci44LjIuMTQ3XzE